Internet access, usage and trust among medical professionals in China: A web-based survey - Hairuo Zhou; Jing Zhang; Jing Su (Elsevier, 2020)
Objectives: Social media has changed methods of communication in the medical profession. As part of a "doctor as communicator" strategy, Chinese medical professionals are actively embracing social media, which may have an impact on tense physician-patient relationships in China. This paper aims to examine a pattern of Internet access, Internet usage, and trust among Chinese medical professionals and further explores the reasons for these relationships on an individual level. Designs: A web-based questionnaire was designed, based on a media literacy model, and was divided into 3 dimensions: public information, general medical information, and specialty information. After a two-round pilot study, 1001 physicians were included. Additionally, 4 interviewees were chosen to participate in in-depth interviews and content analysis was performed. Data were analyzed using SPSS 25.0. Results: Findings showed that new media has become a major approach for medical professionals in China to retrieve and get access to various information. However, they still trust traditional media (n = 1001, P < 0.01) and professional journals more (n = 1001, P < 0.01). Internet access, usage, and trust were positively correlated (r = 0.185-0.344, P < 0.01). Regarding usage habits, 47.66% of the participating physicians would practice science popularization through their new media accounts and 71.23% would forward approved health information within their professional realm. A validated instrument can be provided for further related studies. Conclusions: Science popularization is a specific usage of new media among Chinese medical professionals, through which they have achieved new authority and empowered communication because of self-media. To some extent, physician-patient relationships in China can be improved because this online interaction is conducive to building harmonious and lasting offline physician-patient relationships.